Service quality of social insurance industry and customer satisfaction from Malaysian perspective: customer knowledge as a moderator - Rajan, Dinesh Kumar Saundra; Abdul Aziz, Fadzli Shah; Abdul Manab, Norlida (International Academic Research Journal All rights reserved, 2018)
Social insurance has an important role on delivering welfare-economics benefits to its customer in the course of occupational accidents. The increases of occupational accidents in Malaysia put stress on the social insurance to deliver a good services in order to improve its customer satisfaction. In this study, service quality which consists of tangibles, reliability, responsiveness, assurance and empathy (Parasuraman et al., 1988) seems to be an appropriate factor that social insurance organization need to tackle in carrying out their duties effectively and efficiently. Meanwhile, customer knowledge which measure the performance of an organization on delivering knowledge of product and services to the customer (Ensign & Gittelson, 1988) can act as a catalyst for customer satisfaction that will support the implementation of service quality in social insurance. Therefore, this conceptual paper attempts to examine the role of customer knowledge as a moderator on the relationship service quality of social insurance and customer satisfaction in Malaysian context.